A Synergic Strategy to Characterize the Habitability Conditions of Exoplanets Hosted by Solar-Type Stars - Reda, Raffaele; Di Mauro, Maria Pia; Giovannelli, Luca; Alberti, Tommaso; Berrilli, Francesco; Corsaro, Enrico (Frontiers in Astronomy and Space Sciences, 2022)
We present a new synergic strategy that merges the potential of asteroseismology with solar space weather/climate techniques in order to characterize solar-like stars and their interaction with hosted exoplanets. The method is based on the use of seismic data obtained by the space missions Kepler/K2 and TESS Transiting Exoplanet Survey Satellite, coupled with stellar activity estimates deduced from ground-based campaigns (e.g., Mount Wilson Observatory HK Project). Our investigation allows us to determine not only highly accurate fundamental parameters of the mother star and its orbiting planet, but also to study the stellar magnetic activity and the star-planet interaction: in analogy to the Sun-Earth system, it is possible to infer the mean stellar wind acting on the exoplanet in order to define the conditions of the exoplanetary environment and the erosion of its atmosphere with an impact on the habitability of the planet.